Maternal weight and paediatric health use: mediating role of adverse birth outcomes: a retrospective cohort study - Currie, Lisa M.; Brown, Hilary K.; Potter, Beth K.; Hawken, Steven; Coyle, Doug; Wen, Shi W.; Walker, Mark; Gaudet, Laura (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Maternal pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) above or below recommendations have been associated with increased paediatric health service utilization as well as increased risk of adverse birth outcomes, including small for gestational age (SGA) and preterm birth (PTB). SGA and PTB are associated with numerous adverse health outcomes in the child, including delayed growth, motor and cognitive impairment. Previous research has identified birth weight and gestational age on the causal pathway in the association between maternal pre-pregnancy BMI and child hospital admissions, there are no studies to date to quantify this relationship across other areas of health service utilization, nor the impact of gestational weight gain. This study aimed to assess if SGA or PTB partially explain the association between maternal weight and paediatric health service utilization. Methods The study population consisted of all women who delivered a singleton, live infant in Ontario between 2012 and 2014, and was assembled from data contained in the provincial birth registry. Health service utilization over the first 24 months following birth was examined by linking data from the registry with other provincial health administrative databases housed at ICES. The mediating roles of PTB and SGA were assessed using the Baron-Kenny method and causal mediation analysis. Results A total of 204,162 infants were included in the analysis of maternal pre-pregnancy BMI and 171,127 infants were included in the GWG analysis. The small magnitude of association between maternal BMI and paediatric health service utilization impacted our ability to estimate the indirect effect of maternal BMI through adverse birth outcomes (adjusted indirect effect = 0.00). 56.7% of the association between below recommended GWG and increased hospitalizations was attributed to PTB, while 6.8% of the association was attributed to SGA. Conclusion Paediatric hospitalizations may be partially attributable to PTB and SGA in children born to mothers with below-recommended GWG. However, maternal weight also appears to be related to increased paediatric health service utilization independent of PTB and SGA.